SIMULASI PENDISTRIBUSIAN BUAH KELAPA SAWIT DI PT. MITRA AUSTRAL SEJAHTERA NADOK PARINDU KABUPATEN SANGGAU KALIMANTAN BARAT - Agus Ramdhani Nugraha (JURNAL MANAJEMEN INFORMATIKA (JUMIKA), 2014)
In globalization era which fast progressively, almost every company use information system in each their office. This matter so very good, because it can quicken about times and works. Technology is felt most fast its growth, one of them computerazation area. Computer as represent appliance assist to human being continue to be complete so that progressive easy to operating it, either from software facet and also is hardware.PT. Mitra Austral Sejahtera Nadok Parindu sub-province of Sanggau West Kalimantan is a company which active in plantation, a specialy plantation of kelapa sawit (coconut of sawit). In running its activity, this company often use interaction with all customer or client and also with company of transportation, it’s of course stand in need of information which quickly, precisely and accurate. Pursuant the mentioned, writer try to give solution by making distribution simulasi of coconut fruit of.Having completed this report, writer hope this system can be used to assist for improve existing system which have there’s or using this time.Keyword: Simulation, System, Distribution